2018
DOI: 10.1098/rsos.171743
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids modulate gastrointestinal microbiome in a wild bird

Abstract: It has recently been hypothesized that stress exposure (e.g. via glucocorticoid secretion) may dysregulate the bacterial gut microbiome, a crucial ‘organ' in animal health. However, whether stress exposure (e.g. via glucocorticoid secretion) affects the bacterial gut microbiome of natural populations is unknown. We have experimentally altered the basal glucocorticoid level (corticosterone implants) in a wild avian species, the yellow-legged gull Larus michahellis, to assess its effects on the gastrointestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 46 publications
5
98
2
Order By: Relevance
“…GCs have been shown to alter the composition of gut microbes, which are linked to changes in gut and brain function. (31,32,102,113) For example, stress, which elevates serum corticosteroid levels, alters the microbiome and reduces levels of intestinal lactobacilli and increases the growth of E. coli and pseudomonas. (102,113) Stress also increases intestinal bacterial expression of virulence genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GCs have been shown to alter the composition of gut microbes, which are linked to changes in gut and brain function. (31,32,102,113) For example, stress, which elevates serum corticosteroid levels, alters the microbiome and reduces levels of intestinal lactobacilli and increases the growth of E. coli and pseudomonas. (102,113) Stress also increases intestinal bacterial expression of virulence genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the direct effects of GC on bone, GCs also affect other organ systems that can further influence bone health. Especially relevant to the present study, GCs can alter intestinal microbiota composition in animal models …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although no primate study has yet tested this hypothesis, in wild red squirrels ( Tamiasciurus hudsonicus ) it was found that fecal glucocorticoid metabolites were negatively correlated with bacterial diversity and that there was a positive relationship over time between fecal glucocorticoid metabolite concentrations and bacterial abundance of Pasteurellaceae, a family with known epizootic pathogens (Stothart et al, ). On the contrary, experimentally elevated basal glucocorticoid levels reduced pathogenic bacteria, including Mycoplasma and Microvirga , in the intestines of yellow‐legged gulls ( Larus michahellis ; Noguera, Aira, Pérez‐Losada, Domínguez, & Velando, ).…”
Section: Microbial Endocrinology Of the Stress Responsementioning
confidence: 99%
“…As the mediator between a vertebrate's perception of its environment and a suite of physiological responses, the HPA axis provides a useful universal measure of how host responses to environmental stimuli could shape the microbiome. Change in the HPA axis has been demonstrated to affect the microbiome in laboratory models [16][17][18] and in free-living wildlife [19][20][21][22]. However, the laboratory approach of comparing control and stressor-exposed animals under highly controlled conditions that lack ecological reality makes extrapolating results to the free-living organisms difficult.…”
Section: Introductionmentioning
confidence: 99%